Performing COVID-19 Control in Finland: Interpretative Topic Modelling and Discourse Theoretical Reading of the Government Communication and Hashtag Landscape - Koljonen, Juha; Palonen, Emilia (Frontiers in Political Science, 2021)
This article discussses discursive transformations in the performance of the government and the ‘hashtag landscape’, studying Twitter discussions and the female-led government of one of the youngest Prime Ministers in the world, Sanna Marin of Finland. Among countries in Europe, Finland has been, in the period of analysis of March 2020 to January 2021, one of the least affected by the Covid-19 pandemic. Our datasets from both Twitter discussions and the government’s press conferences in 2020 reveal which were the emerging topics of the pandemic year in Finland and how they were discussed. We observe a move from consensual governmental political control to control in the hands of the authorities and Ministers responsible, performing a different basis for the pandemic. On the ‘hashtag landscape’, face masks continually emerge as an object of debate. They become not only a point of trust and distrust that the government cannot ignore. In terms of comparative governance, this article also notes how the emergency powers legislation shifted control to the government from regional authorities and municipalities in spring 2020, and by that autumn those powers were returned to regional and local bodies. We recognize several themes that were contested, and the discursive field’s transformations and interplay with the authorities. This article develops an original approach to reading thematical data longitudinally for both social media discussions and government performance, a key contribution of this article to the state of the art is a novel methodological framework that combines rhetoric-performative discourse theory with interpretive instrumentalism: topic modelling with qualitative research. By analyzing control during the Covid-19 situation, we address the challenges of social media research and illustrate the need for a dialogical approach with the research materials. Understanding the performance of elected officials in controlling a crisis and interconnected debates among the hashtag publics or on the hashtag landscapes may be key to perceiving contemporary politics, where discursive shifts in performance and contestation are important objects of study.